The emerging role of long non-coding RNAs in renal cell carcinoma progression and clinical therapy via targeting metabolic regulation - Gao, Xingyu; Zhang, Haiying; Zhang, Chang; Li, Minghe; Yu, Xiao; Sun, Yanan; Shi, Yingai; Zhang, Hongxia; He, Xu (Frontiers in Pharmacology, 2023)
Renal cell carcinoma (RCC) is the most frequent renal malignancy in the world, and its incidence is increasing year by year. RCC is a well-known drug resistant tumor, and the treatment methods are limited. Most patients with RCC are discovered at the advanced stage, and thus have poor prognosis even after treatment. Therefore, it is very urgent to find new markers for the diagnosis and treatment of RCC. Accumulating evidence shows that lncRNAs participate in the occurrence and progression of RCC, which is achieved by the lncRNA-miRNA-mRNA axis. It is widely known that metabolic defect is an essential pathogenesis in RCC. As is the case with other tumors, RCC can satisfy the demands of cancerous cells for uncontrolled proliferation through aerobic glycolysis. However, whether lncRNAs can modulate RCC progression through metabolic pathway is still not clarified. Taken together, this review mainly summarized the metabolic regulatory mechanisms of lncRNAs in RCC progression, especially their roles in glucose metabolism, lipid metabolism, amino acid metabolism and mitochondrial dynamics, as well as the clinical applications of lncRNAs via targeting metabolism in RCC therapy. It will provide the new targets and approaches for early clinical diagnosis, treatment and prognosis of RCC.